(untitled) (Islamic Sciences Journal, 2023)
Signs of creativity appeared from Abi Al-Alaa Al-Maari, through the aesthetic of the poetic discourse that was characterized by the presence of language and its connotations clearly. It is evident that the rhetorical effort has led to the existence of many concepts, including the addressee who produces the speech, and the addressee who receives and interacts with him From the above mentiond sayings, there are starting points and directions of discourse in the poet’s poetry, which are clear in his poetic poems, by relying on his language, the connotations thereof, and the contents of the literary product from a precise look at the events that have a clear impact on the emergence of such poetry through explanation, and the generation of meanings, As well as the rhetorical presence on a large scale